2016
DOI: 10.1105/tpc.16.00310
|View full text |Cite
|
Sign up to set email alerts
|

Local Auxin Biosynthesis Mediated by a YUCCA Flavin Monooxygenase Regulates Haustorium Development in the Parasitic Plant Phtheirospermum japonicum

Abstract: Parasitic plants in the Orobanchaceae cause serious agricultural problems worldwide. Parasitic plants develop a multicellular infectious organ called a haustorium after recognition of host-released signals. To understand the molecular events associated with host signal perception and haustorium development, we identified differentially regulated genes expressed during early haustorium development in the facultative parasite Phtheirospermum japonicum using a de novo assembled transcriptome and a customized micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
126
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 102 publications
(145 citation statements)
references
References 84 publications
(113 reference statements)
7
126
4
Order By: Relevance
“…However, QR2 transcripts exhibited strong PhQ-coexpression in P. aegyptiaca (kPhQ =4) and S. hermonthica (kPhQ =3)( Fig. 3E), in line with QR2 responsiveness to HIFs during haustorium formation of Phtheirospermum japonicum and S. asiatica (23,24). These findings, along with the reported PM-association of AtQR2s (25), support QR2 involvement in the PM redox system.…”
supporting
confidence: 77%
“…However, QR2 transcripts exhibited strong PhQ-coexpression in P. aegyptiaca (kPhQ =4) and S. hermonthica (kPhQ =3)( Fig. 3E), in line with QR2 responsiveness to HIFs during haustorium formation of Phtheirospermum japonicum and S. asiatica (23,24). These findings, along with the reported PM-association of AtQR2s (25), support QR2 involvement in the PM redox system.…”
supporting
confidence: 77%
“…Reverse genetics in parasitic plants is effective only in few chlorophyllous parasitic plants to date (Ishida et al, 2011, 2016; Bandaranayake et al, 2012). These plants are indeed able to develop without a host, which facilitates the production of transgenic lines.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, wound-inducible protein kinases that constitute pathogen recognition or calcium signaling are activated within 3 h. It is also interesting to note that genes annotated as responsive to other stresses such as heat, chitin, or biotic stimulus are strongly activated at 1 h after wounding. Previous studies have reported that heat stress induces somatic embryogenesis in some plant species (Fehér 2015), and biotic interactions can trigger cellular proliferation and reprogramming during symbiosis and parasitism (Suzaki et al, 2012;Ishida et al, 2016). It will be thus interesting to test if these stress-induced developmental changes share regulatory mechanisms with wound-induced callus formation.…”
Section: Global Transcriptional Changes During Wound-induced Callus Fmentioning
confidence: 99%